Integrating oral health into pediatric nursing practice: Caring for kids where they live. Issue 2 (27th February 2015) - Spurr, Shelley; Bally, Jill; Ogenchuk, Marcella
Abstract Purpose The purpose was to identify the factors influencing pediatric oral health and describe the Caring for Kids Where They Live program. Conclusions In North America, the burden of pediatric oral disease is significant. Despite evidence to this effect, oral health is an often‐neglected aspect of pediatric nursing care. The Caring for Kids Where They Live program has successfully integrated oral health into pediatric nursing care as evidenced by increased accessibility of health care, pathways for care, and disease prevention. Practice Implications Pediatric nurses can address oral health disparities by integrating an oral health assessment tool as well as interprofessional follow‐up and referral processes in practice.